Nasopharyngeal cancer in non-endemic areas: Impact of treatment intensity within a large retrospective multicentre cohort. (December 2021) - Bossi, Paolo; Trama, Annalisa; Bernasconi, Alice; Grisanti, Salvatore; Mohamad, Issa; Galiana, Isabel L.; Ozyar, Enis; Franco, Pierfrancesco; Vecchio, Stefania; Bonomo, Pierluigi; Cirauqui, Beatriz C.; El-Sherify, Mustafa; et al.
Abstract: Aim: Recommendations for managing patients with nasopharyngeal carcinoma (NPC) in non-endemic areas are largely derived from studies conducted in endemic areas. We analysed the impact of treatment approaches on survival in non-endemic areas. Methods: In an international, multicentre, retrospective study, we analyse consecutive patients with NPC diagnosed between 2004 and 2017 in 36 hospitals from 11 countries. Treatment was categorised as non-intensive (NIT), including radiotherapy alone or concomitant chemoradiotherapy (cCRT), and intensive (IT) including cCRT preceded by and/or followed by chemotherapy (CT). The impact of IT on overall survival (OS) and disease-free survival (DFS) was adjusted for all the available potential confounders. Results: Overall, 1021 and 1113 patients were eligible for overall survival (OS) and disease-free survival (DFS) analyses, respectively; 501 and 554 with Epstein Barr-encoded RNA (EBER) status available. In the whole group, 5-year OS was 84% and DFS 65%. The use of NIT was associated with a risk of death or recurrence 1.37 times higher than patients receiving IT. Patients submitted to NIT and induction CT + concurrent concomitant chemo and three-dimensional Conformal Radiation Therapy (3DCRT) had a risk of death or recurrence 1.5 and 1.7 times higher than patients treated with induction CT + cCRT with intensity-modulated radiotherapy (IMRT), respectively. The IT had no impact on OS in neither patients with EBER+ nor in patients with EBER-; IT showed better DFS in EBER+ but not in patients with EBER-. Conclusions: In low-incidence areas,  patients with NPC treated with induction CT followed by concurrent IMRT cCRT achieved the highest DFS rate. The benefit of IT on DFS was restricted to patients with EBER+, suggesting that additional therapy offers no advantages in EBER- cases. Highlights: Nasopharyngeal cancer 5-years OS and DFS rates, in non-endemic area, are 84% and 65%. Intensive treatment approaches improve DFS in patients with locally advanced cancers. The benefit of intense treatment on DFS was restricted to patients with EBER+.